MANAJEMEN ASET DI KANTOR DINAS PENDIDIKAN KOTA SURAKARTA - Adam Pandu Priyo Prakosa; Hery Sawiji; Anton Subarno (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2021)
This study aims to determine the implementation of asset management in the Surakarta Education Office, the obstacles, and the efforts to overcome obstacles in asset management at the Surakarta Education Office. This research is a qualitative research with a case study approach. Data obtained from informants, events, documents with purposive snowball sampling. The validity of the data was checked by methods triangulation and sources triangulation. The results of the study: (1) asset management at the Surakarta Education Office is carried out one-stop centered on the General and Personnel Subfield, while the asset management activities carried out are needs planning, procurement, inventory, legal audit, assessment, operation and maintenance of assets, and asset disposal, (2) obstacles in asset management at the Surakarta Education Office are assets not being approved to be procured, and communication among the divisions that has not been good, (3) efforts made by the Surakarta Education Office to overcome these obstacles are by submitting the procurement of assets that have not been approved in the next procurement period on a priority scale, and procuring assets by leasing. The next effort is re-communicating information about asset management to each division, checking and updating asset data so that assets are recorded properly.